Segmentation Using Attitude Change Theories - Sridhar, G. (Indian Journal of Marketing, 2005)
Attitude formation and change theories in consumer behaviour literature have received wide attention till date. These theories especially attitude formation theories are used by marketers to segment, target and position products and services. However, little evidence exists in the use of attitude change theories for segmenting, and targeting. This paper addresses the above concern. The paper attempts at understanding the use of attitude change theories for segmentation and targeting by using nicotine patches as an example. The choice of the product is apt considering the growing importance of anti tobacco movement across the globe. The paper briefly describes how attitude forms and changes, followed by description of nicotine patches, segmentation and targeting scheme for nicotine patches using attitude change theories.